Pentingnya BPSK Terhadap Perlindungan Konsumen - Utomo, Ksatrio Budi; Zubaedah, Rahmi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this service is to provide understanding to friends about the importance of BPSK's existence as an effort to protect consumers from the law. The method used is through outreach and continued discussions with friends. Some of the problems faced by the participants were related to the lack of information and socialization regarding consumer and BPSK legal protection, these problems can be overcome by implementing counseling so that it can increase friends' insights regarding various aspects of consumer legal protection including the existence of BPSK in preventive and repressive efforts in resolving consumer disputes as a general consumer protection effort.